Characterizing the variability of food waste quality: A need for efficient valorisation through anaerobic digestion. (April 2016) - Fisgativa, Henry; Tremier, Anne; Dabert, Patrick
Highlights: A statistical analysis of food waste data from 70 scientific papers was performed. High variability of food waste characteristics was stated out. Geographical origin, collection source and season explain 24% of the variations. FW generally show a high biodegradable potential with high VS, COD and BMP. Some attention points for AD are: pH, TAN, carbohydrates and cellulose contents. Abstract: In order to determine the variability of food waste (FW) characteristics and the influence of these variable values on the anaerobic digestion (AD) process, FW characteristics from 70 papers were compiled and analysed statistically. Results indicated that FW characteristics values are effectively very variable and that 24% of these variations may be explained by the geographical origin, the type of collection source and the season of the collection. Considering the whole range of values for physicochemical characteristics (especially volatile solids (VS), chemical oxygen demand (COD) and biomethane potential (BMP)), FW show good potential for AD treatment. However, the high carbohydrates contents (36.4%VS) and the low pH (5.1) might cause inhibitions by the rapid acidification of the digesters. As regards the variation of FW characteristics, FW categories were proposed. Moreover, the adequacy of FW characteristics with AD treatment was discussed. Four FW categories were identified with critical characteristics values for AD performance: (1) the high dry matter (DM) and total ammonia nitrogen (TAN) content of FW collected with green waste, (2) the high cellulose (CEL) content of FW from the organic fraction of municipal solid waste, (3) the low carbon-to-nitrogen (C/N) ratio of FW collected during summer, (4) the high value of TAN and Na of FW from Asia. For these cases, an aerobic pre-treatment or a corrective treatment seems to be advised to avoid instabilities along the digestion. Finally, the results of this review-paper provide a data basis of values for FW characteristics that could be used for AD process design and environmental assessment.